Reformasi Konstitusi Indonesia: Fenomena Transisi Kekuasaan - Susanto Polamolo (UIN Sunan Kalijaga Yogyakarta, 2013)
One of the main demands of the momentum of reform in Indonesia is aconstitutional 1945 amendment, is due to the pre-reform constitution have not been able to achieve democratic governance, and even tended to authoritarian and centralized.And has devastated all pillars of democracy, weak law enforcement and respect for human rights, as well as the role of local fecklessness. Exactly in this section, the constitutional reform carried in one hand bring a change in the structure of the political system, but noted the issue of overlapping of authority between state institutions which of course can affect performance and cultur democratization which would be built.Presumably indeed, constitutional reform in addition to opening democratic space, also opened a dimensional complexity of the constitutional problem.